Knowledge of General Health Law with Respect to Blood Transfusions by Physicians and Patients Jehovah witnesses in Hospital Dr. Dario Contreras of Dominican Republic - Díaz Santana, Elsa (Acta Bioethica, 2010)
This study evaluates up to which degree physicians of Hospital Dr. Dario Contreras of Dominican Republicknow, respect, inform and apply the General Health Law in relation to the right of Jehovah witness patients to refuse beingblood transfused (respect to their autonomy). It also evaluates whether Jehovah witnesses know General Health Law and inwhich degree they have been benefited by putting it into practice. The study reveals that Jehovah Witnesses do not knowthe law.